The Role Of Prosecutors In Handling Eradication Of Corruption Crime - Agustinus Dian Leo Putra; Gunarto Gunarto (Law Development Journal, 2021)
The purpose of this study is to examine and analyze the role of the Prosecutor's Office in handling criminal acts of corruption judicially. In this paper the author uses a normative juridical method. Based on the research, it can be concluded that the duties and functions of the prosecutor as an investigator of criminal acts of corruption are in accordance with the provisions of Article 284 paragraph (2) of the Criminal Procedure Code, the Prosecutor is still authorized to carry out investigations of special crimes in this case corruption. Eradication of corruption is to rely on the consistent treatment of Law on the eradication of corruption. 20 of 2001 concerning amendments to Act No. 31 of 1999 concerning the eradication of corruption. The prosecutor as an investigator concurrently serves as a public prosecutor in handling corruption crimes. Exceptions based on Article 284 paragraph (2) of the Criminal Procedure Code. The Criminal Procedure Code has relinquished the investigative authority from the prosecutor's office, and has been fully assigned to the police